Gut Health and Its Association with Wellbeing and Nutrient Intake in Community-Dwelling Older Adults - Frida Fart; Lina Tingö; Stina Engelheart; Carl Mårten Lindqvist; Robert J. Brummer; Annica Kihlgren; Ida Schoultz (Gastroenterology Insights, 2022)
Many of the increasing number of community-dwelling older adults will need increased healthcare in the future. By characterising gut health and its association with wellbeing and nutrient intake in this population, we aim to recognise areas along the gut–brain axis through which the health of community-dwelling older adults might be promoted. In this cross-sectional observational study, validated questionnaires were used to assess gut health, nutrient intake, and wellbeing in 241 community-dwelling older adults (≥65 years old). In total, 65% of the participants experienced at least one gastrointestinal symptom, of which females had more abdominal pain and constipation, while the oldest old (i.e., ≥80 years old) had more diarrhoea. Increased gastrointestinal symptoms correlated with more stress, anxiety, depression, and a decreased quality of life, in addition to dyspepsia which correlated with a lower E% of protein. Most of the participants did not reach the recommended intake for protein, fibre and polyunsaturated fats. Males had a lower intake of protein (E%) and fibre (g/MJ) than females, and the oldest old had a lower E% of protein than younger older adults. In conclusion, our results demonstrate that gastrointestinal symptoms are common, and most of the study participants had an imbalanced macronutrient intake, which could be a target for future possible dietary interventions to improve overall health.